Effect of Al2O3 and ZrO2 Filler Material on the Microstructural, Thermal and Dielectric Properties of Borosilicate Glass-Ceramics - Dilara Arıbuğa; Oğuz Karaahmet; Özge Balcı-Çağıran; Buğra Çiçek (Micromachines, 2023)
Various glass-ceramics are widely used or considered for use as components of microelectronic materials due to their promising properties. In this study, borosilicate glass was prepared using the powder metallurgical route and then mixed with different amounts of Al2O3 and ZrO2 filler materials. Glass-ceramics are produced by high-energy ball milling and conventional sintering process under Ar or air. In this study, the effects of different filler materials and different atmospheres on the microstructural, thermal and dielectric properties were investigated. The data showed that ZrO2 filler material led to better results than Al2O3 under identical working conditions and similar composite structures. ZrO2 filler material significantly enhanced the densification process of glass-ceramics (100% relative density) and led to a thermal conductivity of 2.904 W/K.m, a dielectric constant of 3.97 (at 5 MHz) and a dielectric loss of 0.0340 (at 5 MHz) for the glass with 30 wt.% ZrO2 sample. This paper suggests that prepared borosilicate glass-ceramics have strong sinterability, high thermal conductivity, and low dielectric constants, making them promising candidates for microelectronic devices.